2022
DOI: 10.1097/j.pain.0000000000002588
|View full text |Cite
|
Sign up to set email alerts
|

A nigra–subthalamic circuit is involved in acute and chronic pain states

Abstract: Reversal of the attenuated SNrGABA−STNGlu projection mitigates pain-related behaviors in acute and chronic inflammatory pain and neuropathic pain states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…Similarly, we previously reported that SNr neurons innervated by the STN partially mediate hyperalgesia in parkinsonian mice 20 . Contrary to these studies 20,61 , but similar to another study 37 , we observed that stimulation of SNr neurons led to analgesic effects. These results suggest that SNr neurons are diverse in terms of their involvement in pain perception, depending on which neural pathway they belong to.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Similarly, we previously reported that SNr neurons innervated by the STN partially mediate hyperalgesia in parkinsonian mice 20 . Contrary to these studies 20,61 , but similar to another study 37 , we observed that stimulation of SNr neurons led to analgesic effects. These results suggest that SNr neurons are diverse in terms of their involvement in pain perception, depending on which neural pathway they belong to.…”
Section: Discussionsupporting
confidence: 58%
“…That is, those innervated by the LPB and STN may facilitate the transmission of pain signals, whereas those innervating the STN suppress pain perception. Indeed, two subsets of SNr neurons that respectively innervate STN neurons and are innervated by STN neurons are largely separated 37 . Taking the previous studies together with our current finding, we propose that SNr GABA neurons receive pain-related information from the LPB and, in turn, regulate the downstream STN-LPB pathway and pain responses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations